An Inquiry into the Literacy Practices of Children with Autism, in Mainstream Primary Schools in the Republic of Ireland - O'SÍORÁIN, CAROL-ANN ROISIN (Trinity College Dublin. School of Education. Discipline of Education, 2018)
AN INQUIRY INTO THE LITERACY PRACTICES OF CHILDREN WITH AUTISM, IN MAINSTREAM PRIMARY SCHOOLS IN THE REPUBLIC OF IRELAND Carol-Ann O?S?or?in ABSTRACT The increased prevalence of pupils with autism across the United States and Europe has highlighted the need for appropriate educational strategies and placement options. The Department of Education and Skills, Ireland and the United Kingdom, have called for an increase in the literacy skills and outcomes for pupils with autism. International reviews of literature on teaching and learning have revealed a dearth of research on literacy in this pupil cohort internationally. Parents and educators have raised concerns as to the appropriateness and adequacy of provision, and in so doing; they draw attention to the quality of teaching and learning for children with autism. In response, this study aimed to inquire critically into the literacy skills and practices for and of children with autism in mainstream primary schools in Ireland. The objective was to provide an insight into the literacy opportunities and encounters of these children during the school day and to illicit the perceptions and experiences of parents and teachers relating to literacy teaching and learning. This qualitative, collective case study provides an emic perspective and an appreciation of literacy within specific settings (n=7), and communicates the everyday reality of teaching and learning of literacy for pupils (n=34) with autism. Empirical materials were generated through classroom observations (n=63) and semi-structured interviews with parents (n=24) and teachers (n=11). The case study approach allowed for an in-depth study and interpretation of the phenomenon of teaching within the bounded case of variables such as age and setting. A sociocultural perspective supports the theory that language and literacy develops through the interplay between the social and cultural relationship experienced by the pupil in context with his environment. Key findings relate to: ? An outmoded definition of literacy by teachers, and a disconnect between teachers and parents in their ideology of being literate ? An imbalance in the practices and experience of children with autism in all elements and modes of literacy ? A restriction in the movement and inclusion of pupils with autism across the school and in literate engagement with their peers ? A significant absence in the role of play as a pedagogical tool to advance literacy The findings of this study indicate that a significant focussed approach to teacher education and continuing professional development is needed in literacy teaching and learning. A broader conceptualisation of literacy practices needs to embrace being numerate as a form of being literate. The use of information technology as a mode for exploring the literate behaviours of pupils with autism needs greater attention and position within the pedagogical practices of the teacher. Echoic behaviours of children with autism may demonstrate communicative intent and need to be observed, evaluated and acknowledged. Greater inclusive opportunities are needed for children with autism to build literacy practices through play and social experiences. As special classes and units are a complex feature of current and future provision for pupils with autism this research suggests that a school wide culture of accepting and valuing pupils among their peers is essential. This study is of importance to current research on evidenced-based practices, curricula and interventions for children with autism in mainstream primary schools in Ireland. It provides a profile of literacy practices of children with autism that is unique to previous research.
APPROVED
Keywords: Autism, teaching and learning, literacy, education, Inclusion